Flowering, fruiting and physiology of apple tree under different irrigation levels in the Brazilian semiarid region - de Oliveira, Cíntia Martins; Simões, Welson Lima; Lopes, Paulo Roberto Coelho; da Silva, José Bezerra; Araújo, Emanoel Jurema; Cavalcante, Bruna Lais Silva (Comunicata Scientiae, 2017)
The objective of this study was to evaluate the effect of different irrigation levels on flowering, fruit set, carbohydrate and protein content and gas exchange, of apple varietiesin the Brazilian semiarid region. The experimental design was a randomized block with split plots with five replications and four plot irrigation levels (60, 80, 100, and 120% of the reference evapotranspiration (ETo)) and the subplots with two cultivars (Juliet and Princess). As a result, it was found that the number of flowers (NFL), fruits (NFR), shoot percentage (SP) and fruit set (FS) were higher in cv. Juliet. The number of buds (NB) and the fertility index (FI) were higher in cv. Princess. With regard to metabolites, reducing sugar content (RS) had no significant effect among cultivars. The non-reducing sugar content (NRS), total soluble sugar (TSS) and total soluble proteins (TSP) were higher in cv. Princess. As for irrigation depths, TSP, sprouting, flowering and fruit set increased along with the amount of water applied, while the RS, NRS and TSS contents had the opposite behavior.